A new species of Parafimbrios from northern Vietnam (Squamata: Xenodermatidae) - Ziegler, Thomas; Ngo, Hai Ngoc; van Pham, Anh; Nguyen, Tham Thi; Le, Minh Duc; Nguyen, Truong Quang (Zootaxa, 2018)
A second species of the previously monotypic snake genus Parafimbrios is described from Lai Chau Province, northern Vietnam, based both on molecular and morphological evidences. Parafimbrios vietnamensis sp. nov. is characterized by a combination of the following characters: 1) rostral laterally with two raised, curved edges; the upper one, together with a horizontal curved ridge of tissue, separate the rostral from the internasals; 2) nasal in contact zone with rostral with curved raised edge; 3) nasal in contact zone with supralabials each with two small oblique, curved raised edges located above first and second as well as above second and third supralabials; 4) suture between the internasals much longer than that between the prefrontals; 5) supralabials 8, with the first four bearing raised edges; 6) infralabials 7; mental and anterior three to four infralabials with raised edges; 7) temporals 4+4–5; 8) 35–33–29 dorsal scale rows; 9) laterally rounded ventrals 164; 10) unpaired subcaudals 49; 11) total length of at least 266 mm in males (with a tail length of 44 mm, and a tail / total length ratio of 0. 165). This discovery brings the total number of taxa of the family Xenodermatidae in Vietnam to seven species: Achalinus ater, A. rufescens, A. spinalis, Fimbrios klossi, F. smithi, Parafimbrios lao, and P. vietnamensis.